Alginate Polymerization and Modification Are Linked in Pseudomonas aeruginosa - M. Fata Moradali (American Society for Microbiology, 2015)
ABSTRACT The molecular mechanisms of alginate polymerization/modification/secretion by a proposed envelope-spanning multiprotein complex are unknown. Here, bacterial two-hybrid assays and pulldown experiments showed that the catalytic subunit Alg8 directly interacts with the proposed copolymerase Alg44 while embedded in the cytoplasmic membrane. Alg44 additionally interacts with the lipoprotein AlgK bridging the periplasmic space. Site-specific mutagenesis of Alg44 showed that protein-protein interactions and stability were independent of conserved amino acid residues R17 and R21, which are involved in c-di-GMP binding, the N-terminal PilZ domain, and the C-terminal 26 amino acids. Site-specific mutagenesis was employed to investigate the c-di-GMP-mediated activation of alginate polymerization by the PilZAlg44 domain and Alg8. Activation was found to be different from the proposed activation mechanism for cellulose synthesis. The interactive role of Alg8, Alg44, AlgG (epimerase), and AlgX (acetyltransferase) on alginate polymerization and modification was studied by using site-specific deletion mutants, inactive variants, and overproduction of subunits. The compositions, molecular masses, and material properties of resulting novel alginates were analyzed. The molecular mass was reduced by epimerization, while it was increased by acetylation. Interestingly, when overproduced, Alg44, AlgG, and the nonepimerizing variant AlgG(D324A) increased the degree of acetylation, while epimerization was enhanced by AlgX and its nonacetylating variant AlgX(S269A). Biofilm architecture analysis showed that acetyl groups promoted cell aggregation while nonacetylated polymannuronate alginate promoted stigmergy. Overall, this study sheds new light on the arrangement of the multiprotein complex involved in alginate production. Furthermore, the activation mechanism and the interplay between polymerization and modification of alginate were elucidated. IMPORTANCE This study provides new insights into the molecular mechanisms of the synthesis of the unique polysaccharide, alginate, which not only is an important virulence factor of the opportunistic human pathogen Pseudomonas aeruginosa but also has, due to its material properties, many applications in medicine and industry. Unraveling the assembly and composition of the alginate-synthesizing and envelope-spanning multiprotein complex will be of tremendous significance for the scientific community. We identified a protein-protein interaction network inside the multiprotein complex and studied its relevance with respect to alginate polymerization/modification as well as the c-di-GMP-mediated activation mechanism. A relationship between alginate polymerization and modification was shown. Due to the role of alginate in pathogenesis as well as its unique material properties harnessed in numerous applications, results obtained in this study will aid the design and development of inhibitory drugs as well as the commercial bacterial production of tailor-made alginates.